Effect of cytokinins and auxins on micropropagation of banana (Musa AAA) cv. Albeely by shoot tip explants - H. A. Othman, Mohammed; A. Ali, Mohamed; A. Abdellatif1, Igbal (Gezira Journal of Agricultural Science; Vol 10 No 2 (2012), 2023)
This study was conducted in the plant tissue culture laboratory at the Agricultural Research Corporation (ARC), Wad Medani, Sudan, during the year 2011. The objective was to develop a micropropagation technique for banana, cv. “Albeely”. Two cytokinins i.e. benzylaminopurine (BAP) and isopentenyladenine (2iP) were tested at 0, 2, 4, 6 and 8 mg/l each on micropropagation of the banana cv. Albeely. The results indicated that 4 mg/l was the best concentration for both cytokinins. Two experiments were conducted to determine the best combinations between 4 mg/l of both BAP and 2iP with different concentrations of indole butyric acid (IBA), i.e. 0, 0.2, 0.4, 0.6, 0.8 mg/l on micropropagation of banana. The results indicated that the best shoot morphogenesis was induced on either 4mg/l BAP combined with 0.8 mg/l IBA or 4 mg/l 2iP with 0.6 mg/l IBA.